Sistem Kendali Hidrogen Pada HCl Burner Menggunakan Controller Yokogawa - Suherman, Yohanes Daud; Edilla, Edilla (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2023)
The hydrogen control system is a hydrogen control system in the HCl manufacturing process. This control is needed to control the presence of hydrogen over capacity or low capacity in the HCl burner, resulting in product failure. Hydrogen is one of the first steps for making HCl, which needs to be considered for its parameters, consisting of a control valve, flow transmitter, and pressure transmitter. In this study, a controller can be operated to adjust the hydrogen control valve line opening on the HCl burner. Then to find out the set point value of hydrogen entering the HCl burner, 2 transmitters measure flow and pressure. Furthermore, the signal measured by the transmitter will provide feedback so that the flow and pressure values appear on the controller. To ensure that the parameter data has been observed by comparison between the data on the system and the actual data in the field. From the observational data of this control system, the need for hydrogen for the initial stage of HCl production can be carried out within 1 hour with the control valve opening parameter of 34%, so that by opening the control valve it is known that the flow transmitter indication is 34 kg/hour and the transmitter pressure is 9kPa, so from flow and pressure indications can be used for later stages of the HCl manufacturing process.